Fuzzy Economic Order Quantity (FEOQ) Model with Units Lost Due to Deterioration - Pattnaik, Monalisha (Statistics, Optimization & Information Computing, 2014)
This model investigates the instantaneous fuzzy economic order quantity model by allocating the percentage of units lost due to deterioration in an on-hand inventory by framing variable ordering cost. The objective is to maximize the fuzzy net profit so as to determine the order quantity, the cycle length and number of units lost due to deterioration in fuzzy decision space. For any given number of replenishment cycles the existence of a unique optimal replenishment schedule are proved and mathematical model is developed to find some important characteristics for the concavity of the fuzzy net profit function. Numerical examples are provided to illustrate the results of proposed model which benefit the retailer and this policy is important, especially for wasting of deteriorating items. Finally, sensitivity analyses of the fuzzy optimal solution with respect to the major parameters are also studied.